The Function of the Metals in Regulating Epigenetics During Parkinson’s Disease - Wei, Xiangzhen; Cai, Menghua; Jin, Lifang (Frontiers in Genetics, 2021)
Parkinson’s means Parkinson’s disease, a chronic degenerative disease of central nervous system. The main area which is affected by this disease is motor system. Since it firstly founded by James Parkinson in his 1817 publication, nowadays, people still have lots of questions about this disease. This review mainly summarizes the epigenetics of Parkinson’s. DNA methylation is one of the epigenetic mechanisms of Parkinson’s. During the development of disease, global hypomethylation, hypo-methylatio and hypermethylation happen in different areas of patients. Another epigenetic mechanism is histone modification. What’s more, nowadays people believe that some metals can induce Parkinson’s and Alzheimer disease by modulating epigenetic mechanisms. This review summarizes the relationships between different metals and Parkinson's disease. However, the specific roles of most metals in epigenetics are still unknown, which need further research.